Uji Kinerja Teknologi Kontrol Tepat Guna untuk Peningkatan Kualitas Produksi Sutera Alam - Lilik Sutiarso; Atris Suyantohadi; Hari Purwanto; Radi Radi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2006)
The world demand of raw-silk provides a great opportunity to the development of raw-silk production in Yogyakarta. Recently, only 21% of the overall world demand of raw-silk is fulfilled, whereas Indonesia contributes only 0.1% per year. The main problem is the lack of quality of raw-silk. The optimum growth of silkworm depends on micro environments, i.e. temperature, humidity, aeration, and light intensity. The research aimed at designing an automated “on/off” control technology in the silkworm rearing environmental monitoring in the farming system, while the expected result was high-grade quality of cocoon. In the research, two different conditions of silkworm growing environments were compared, i.e. controlled environment (in the rearing box) and uncontrolled environment. The result indicated that there was increase in the quality of cocoon. Test of cocoons in laboratory showed that the average thickness of cocoons in controlled rearing environment and in rearing environment was 0.033 cm and 0.029 cm, respectively. The percentage of cocoons in controlled rearing environment was higher than cocoons in normal environment.